1981
DOI: 10.1037/h0077775
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal deafferentation and ingestive behavior in rats.

Abstract: For studying the role of orosensory input in the control of ingestive behavior, rats were subjected to varying degrees of trigeminal deafferentation. Somatosensory branches that convey touch, temperature, and pain from the oral cavity were sectioned selectively, and innervation of the muscles of mastication and taste afferents were left intact. Severe intake deficits were produced, which included aphagia, adipsia, and prolonged hypophagia accompanied by a corresponding decrease in body weight. The deficits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 26 publications
5
28
0
1
Order By: Relevance
“…Previous studies in the field have shown and suggested that high levels of ECC, or alike, may result in early decays [2,3], oral-facial pain, reduced dietary intakes, loss of weight or/and sleep, accompanied by a poorer quality of life [2,3,4,5,6]. These conditions could lead to lowered mastication on the occlusal forces, the brain’s neurologic activation, or even some interferences with the metabolism and intellectual development [7,8,9], where the appropriate stimuli are linked to the synapses on the glial (or dendritic) cells for the neuro-physiological functions [10,11]. It has been previously suggested that severe caries and ECC may affect children’s’ verbal skills for proper communications and also weight loss along with certain developmental delays or deficiencies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the field have shown and suggested that high levels of ECC, or alike, may result in early decays [2,3], oral-facial pain, reduced dietary intakes, loss of weight or/and sleep, accompanied by a poorer quality of life [2,3,4,5,6]. These conditions could lead to lowered mastication on the occlusal forces, the brain’s neurologic activation, or even some interferences with the metabolism and intellectual development [7,8,9], where the appropriate stimuli are linked to the synapses on the glial (or dendritic) cells for the neuro-physiological functions [10,11]. It has been previously suggested that severe caries and ECC may affect children’s’ verbal skills for proper communications and also weight loss along with certain developmental delays or deficiencies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of oral somatosensory inputs was indicated by observations of behavior after deafferentation (M iller, 1981;Inoue et al, 1989). On the other hand, extracellular activity recorded in the mandibular division of Gasserian ganglion in rabbits has shown that no intraoral mechanoreceptive afferents discharged during imposed jaw movements or mastication unless their mechanoreceptive ® elds were contacted.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently the tongue moves forward under the food item retained by the teeth and rugae; repe tition of these movements gradually moves the food backwards in the mouth [Thexton, 1984]. The same process for solid food transport has also been de scribed in the rabbit by Ardran and Kemp [1960] and increased gape, when ingesting solids as compared to liquids, has been re ported in rats [Hiiemae and Ardran, 1968], opossums [Hiiemae, 1976], pigs [ProcterGray, personal communication] and liz ards [Smith, 1984], Conversely, a decreas ed gape and an inability to ingest hard food follows a reduction in trigeminal sen sory input, although the ability to ingest semi-solids is retained [Miller, 1981]. The 'additional jaw opening' movement there fore appears to be an important subunit of motor performance [Evarts, 1982] which is triggered by a particular pattern of oral stimulation arising from contact with solid food.…”
Section: Discussionmentioning
confidence: 99%